Water Quality Studies Along the Szilas Stream - Major, Laura; Grósz, János; Sebők, András; Waltner, István (Journal of Central European Green Innovation, 2022)
Sustainable water resource management is one of the most important points in the environment protection. Main objectives of the Water Framework Directive issued by the European Union is the quality and quantity protection of surface and subsurface water. In the case of water bodies, prevention of water pollution is an important objective.Among the natural resources, the available water resources are a highlighted part. Monitoring the quality of surface water can be achieved by implementing regular monitoring programs.The quality of water can usually be determined from the physical, chemical, biological and bacteriological properties of the water. Protection of surface water and wetlands located in urban environments is an important task in terms of ecosystem services. The main objective of this recent study is to assess the environmental condition of Lake Naplás and Szilas stream by examining physical, chemical and biological water quality parameters. During the research program, 4 sampling periods were carried out. We designated 8 sampling points in the study area. The measured water quality parameters included water temperature, water velocity, conductivity, pH value, dissolved oxygen concentration, nitrite, nitrate, ammonia, phosphate, iron, copper, nickel content and a-chlorophyll concentration.
Keywords: chlorophyll-a concentration; water quality; wetlands